2013
DOI: 10.1103/physrevd.88.013008
|View full text |Cite
|
Sign up to set email alerts
|

Unambiguous determination of the neutrino mass hierarchy using reactor neutrinos

Abstract: Determination of the neutrino mass hierarchy in a reactor neutrino experiment at the medium baseline is discussed. Observation of the interference effects between the Ám 2 31 and Ám 2 32 oscillations enables a relative measurement independent of the knowledge of the absolute mass-squared difference. With a 20 kton liquid scintillator detector of the 3%= ffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffiffi E ðMeVÞ p energy resolution, the Daya Bay II experiment at a baseline of $50 km from reactors of tota… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
320
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 236 publications
(331 citation statements)
references
References 34 publications
8
320
1
1
Order By: Relevance
“…The first could be achieved with a medium baseline reactor experiment [8][9][10][11][12][13][14][15][16][17][18][19][20][21] and long baseline accelerator experiments [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]44] could measure all three of them. Atmospheric neutrino experiments could offer alternative ways to accomplish the same.…”
Section: Introductionmentioning
confidence: 99%
“…The first could be achieved with a medium baseline reactor experiment [8][9][10][11][12][13][14][15][16][17][18][19][20][21] and long baseline accelerator experiments [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]44] could measure all three of them. Atmospheric neutrino experiments could offer alternative ways to accomplish the same.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, unlike JUNO [19], the detector can be cylindrical, the PMT coverage can be less than 50% and the scintillator purity does not need to exceed that in present day experiments. Also, as 80% of the events are at energies above 30 MeV and so well above the spallation isotope backgrounds, the detectors do not need to be as deep as JUNO.…”
Section: Jhep01(2016)004mentioning
confidence: 99%
“…JUNO will be located at a distance of 52 km far from Yangjiang and Taishan reactor complexes with a combined power of 36 GW [11]. JUNO will also receive neutrino flux from the existing Daya Bay and planned Huizhou reactors respectively JHEP07 (2014) located 215 km and 265 km far from it.…”
Section: Juno and Reno-50 Experimentsmentioning
confidence: 99%
“…Determining the neutrino mass hierarchy (i.e., normal vs inverted) and precision measurement of the solar mixing parameters θ 12 and ∆m 2 21 are the prime goals of these experiments [9][10][11][12][13][14][15][16][17] (see also [18][19][20][21][22][23][24]). Recently, we have shown that the data from these two experiments can also be employed to probe the superlight sterile neutrino scenario [25].…”
Section: Jhep07(2014)064mentioning
confidence: 99%